The Effects Of Britain’s BREXIT Decision On The Current Geopolitics Of The TRNC (Journal of Oriental Studies, 2018)
The Cyprus is more than fifty years old, and the three guarantor countries are confronted as one ofthe most important issues between Britain, Turkey and Greece and continue to exist as a big problemdespite the changing circumstances and time. Over time, the ‘Cyprus Problem’, which was carried on theInternational platform, has been debated again after Britain’s BREXIT decision. It is once again revealedthat the strategic and geopolitical position of the Turkish Republic of Northern Cyprus (TRNC) in termsof time and the changing international conjuncture in terms of the policy of the UK has become moreimportant. In this study, the effects of Britain’s BREXIT decision on the current geopolitics of the TRNCwill be discussed.